Imaging of Intralabyrinthine Schwannomas: A Retrospective Study of 52 Cases with Emphasis on Lesion Growth - Tieleman, A.; Casselman, J.W.; Somers, T.; Delanote, J.; Kuhweide, R.; Ghekiere, J.; De Foer, B.; Offeciers, E.F. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Only a few case reports and small series of intralabyrinthine schwannomas (ILSs) have been reported. The purpose of this study was to assess prevalence, MR characteristics, location, clinical management, and growth potential/patterns of ILSs in the largest series reported.MATERIALS AND METHODS: Lesion localization, MR characteristics, lesion growth, and clinical management were reviewed in 52 patients diagnosed with an ILS between February 1991 and August 2007 in 2 referral centers. The number of ILSs and vestibulocochlear schwannomas in the cerebellopontine angle/internal auditory canal was compared to assess the prevalence.RESULTS: ILSs most frequently originate intracochlearly, are hyperintense on unenhanced T1-weighted images, enhance strongly after gadolinium administration, and are sharply circumscribed and hypointense on thin heavily T2-weighted 3D images. The scala tympani is more frequently or more extensively involved than the scala vestibuli. Follow-up MR imaging, available in 27 patients, showed growth in 59% of subjects. Growth was seen from the scala tympani into the scala vestibuli and from the scala vestibuli to the saccule and vice versa. Twelve lesions were resected, and the diagnosis of ILS histopathologically confirmed.CONCLUSION: ILSs can account for up to 10% of all vestibulocochlear schwannomas in centers specializing in temporal bone imaging, grow in more than 50%, and are most frequently found intracochlearly, often anteriorly between the basal and second turn. Cochlear ILSs most often originate in the scala tympani and only later grow into the scala vestibuli. Growth can occur from the cochlea into the vestibule or vice versa through the anatomic open connection between the perilymphatic spaces in the scala vestibuli and around the saccule.